Exposure to low concentrations of pesticide stimulates ecological functioning in the dung beetle Onthophagus nuchicornis - Manning, Paul (PeerJ, 2020)
Body-size is an important trait for predicting how species contribute to ecosystem functions and respond to environmental stress. Using the dung beetle Onthophagus nuchicornis (Coleoptera: Scarabaeidae), we explored how variation in body-size affected ecosystem functioning (dung burial) and sensitivity to an environmental stressor (exposure to the veterinary anthelmintic ivermectin). We found that large beetles buried nearly 1.5-fold more dung than small beetles, but that mortality from exposure to a range of concentrations of ivermectin did not differ between large and small beetles. Unexpectedly, we found that exposure to low concentrations of ivermectin (0.01⁠–1 mg ivermectin per kg dung) stimulated dung burial in both small and large beetles. Our results provide evidence of ecological functioning hormesis stemming from exposure to low amounts of a chemical stressor that causes mortality at high doses.